Design of Earthquake Detection System Using MPU6050 and SW420 Sensors with Blynk Platform Integration - Az- Zahra, Dini (Electrical Engineering Departement, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Earthquakes are natural disasters that can cause major damage and even loss of life in a short time. Therefore, an early detection system that can provide warnings before an earthquake occurs is very important to reduce the impact of damage. This study aims to develop an earthquake detection tool that utilizes Internet of Things (IoT) technology. This system uses the SW420 sensor to detect earthquake vibrations and the MPU6050 sensor to measure acceleration and changes in orientation. The method used in this study uses the Research and Development (RnD) method, where this research starts from problem identification, system design, to system testing and evaluation. This system uses ESP32 as a microcontroller to process data from sensors and send the data through the Blynk application in real time. The test results show that this tool is able to detect an earthquake when the magnitude reaches a predetermined minimum limit. With this IoT integration, it is hoped that it can increase community preparedness in facing the threat of earthquakes.